Differences in Social and Mental Well-Being of Long-Term Survivors among People who Inject Drugs and Other Participants in the Swiss HIV Cohort Study: 1980–2018. Issue 1 (January 2020) - Kusejko, Katharina; Marzel, Alex; Nguyen, Huyen; Chaudron, Sandra E; Bachmann, Nadine; Weber, Rainer; Bruggmann, Philip; Roth, Jan A; Bernasconi, Enos; Calmy, Alexandra; Cavassini, Matthias; Bregenzer, Andrea; et al.
Background: People living with HIV who were diagnosed before highly active antiretroviral therapy became available in 1996 and who survived at least 15 years after HIV diagnosis, termed long-term survivors (LTS), form a particularly vulnerable population. We study social, clinical and mental factors of LTS in the Swiss HIV Cohort Study, with a particular focus on people who inject drugs (PWID). Methods: We quantified differences between PWID LTS, and men who have sex with men (MSM) and heterosexual (HET) LTS. Using phylogenetic methods, we distinguished between heterosexual LTS who most likely shared a social network with PWID at the time of infection, termed clusteredHET, and those who did not, termed HET not clustered (HETnc). The analysis was performed using data collected at least 15 years post diagnosis. Results: Overall, 1, 663 of 5, 686 (29.2%) PWID were LTS. We found significant differences between PWID LTS and MSM/HETnc LTS regarding self-reported depression (59.4% versus 43.3%; odds ratio [OR]=1.8; P <0.001), incarceration (30.6% versus 7.0%; OR=6.9; P <0.001) and full work ability (25.4% versus 59.0%; OR=0.27; P <0.001). ClusteredHET were less vulnerable with respect to these variables than PWID LTS but more at risk compared with MSM/HETnc LTS, indicating that clusteredHET are closer to PWID with regard to social and mental aspects compared with all MSM/HETnc. Conclusions: Even more than 15 years post HIV diagnosis, special care for HIV-positive PWID is needed, with emphasis on mental health and social integration of PWID LTS.